PENERAPAN STRATEGI INFORMATION SEARCH PEMBELAJARAN DI SD N 1 DARAT DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI - Rahma Yunisa; Rachelia; Ricky Jonathan; Syarnubi Syarnubi (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
The teacher needs to have initiative and creative thinking in doing PAI learning Then the use of the right strategy in the PAI learning process will affect the activeness and understanding of the students The necessary strategy is the selection of the right learning models and methods in teaching Islamic religious education. Because the use of methods in learning is very important in order to increase the motivation of students to learn The motivation of students to learn will affect the success rate of students' learning. This study examines the strategies used by SD N 1 Darat teachers in the learning process of Islamic religious education and manners with Qodo and Qadar material. The results of the research were obtained through a process of observation, interviews and document recording accompanied by documentation during the learning process. The members studied were teachers and 5th grade students of SD N 1 Darat. based on the research the results confirm that the information search strategy has been successful in creating an effective learning process and creating good interactions between teachers and students. Students also gave a positive response after doing the learning process in Qodo and Qadar material.